Bank-Specific Determinants of Credit Risk for Commercial Banks: An Applied Study of a Sample of Algerian Commercial Banks During The Period 2007 - 2019 - Fatma Benchenna (Dirassat Journal Economic Issue, 2022)
This study aims to monitor a group of factors that causes the credit risk and contributes to the occurrence of non-performing loans problem in the Algerian commercial banks by testing the determinants of credit risk and the explanatory factors of the non-performing loans problem to a sample of Algerian commercial banks during the period 2007-2019, using Panel data models. The main results of the applied study indicate that: The explanatory variables of the credit risk that causes the non-performing loans problem in the Algerian commercials banks, by using the loan loss provisions to total loans index ratio are: the bank size; the Inefficiency ratio and the deposit’s interest rate. The results confirm the validity of the Size Effect Hypothesis, the Skimping Hypothesis and the Deposit Rate Effect Hypothesis.